Formulasi dan Evaluasi Sifat Fisik Serum Daun Sirih Hijau (Piper betle L.) dengan Kombinasi Kolagen Sisik Ikan Gurami (Osphronmus goramy Lac.) sebagai Penghambat Bakteri Acne Vulgaris - Wardani, Diah; Fauzan Nul Hak, Moch; Nurul (Jurnal Medika Farmaka, 2025)
Acne vulgaris is a chronic skin disorder characterized by inflammation due to excessive sebum production and abnormal follicular desquamation. Natural ingredients are considered as promising alternatives, such as green betel leaf (Piper betle L.) containing phenols, flavonoids, and tannins with antibacterial and anti-inflammatory activity. Meanwhile, gourami fish scales (Osphronemus gouramy Lac.) are a source of type I collagen with a triple-helix structure that has potential as an anti-aging agent. This study aimed to formulate and evaluate a serum combining green betel leaf extract and gourami fish scale collagen as an inhibitor of acne vulgaris bacteria. An experimental laboratory study was conducted using three formulas with different concentrations of active ingredients. Physical evaluations included organoleptic properties, homogeneity, pH, viscosity, spreadability, and adhesion on days 7, 14, 21, and 28, along with antibacterial effectiveness testing. The results showed that the best formula was 20% green betel leaf extract combined with 5% collagen, with 83.33% stability parameters fulfilled. The serum produced an inhibition zone of 29.88 mm against acne vulgaris bacteria, although viscosity did not meet the standard range (230–3000 cPs). Thus, this combination has potential as an effective natural anti-acne serum but requires viscosity optimization.